Adaptive resource management and scheduling for cloud computing : Second International Workshop, ARMS-CC 2015, held in Conjunction with ACM Symposium on Principles of Distributed Computing, PODC 2015, Donostia-San Sebastián, Spain, July 20, 2015 : revised selected papers /: Second International Workshop, ARMS-CC 2015, held in Conjunction with ACM Symposium on Principles of Distributed Computing, PODC 2015, Donostia-San Sebastián, Spain, July 20, 2015 : revised selected papers. ([2015]) - Unknown
No abstract available